The value chain of tree tomato (Solanum betaceum) network in Ecuador - Moreno-Miranda, Carlos (2020)
Introduction. The fruit and vegetable sector in Ecuador has shown promising performance in domestic and international markets. Likewise, this sector has faced problems of a social, economic and productive nature in its structure and articulations, which until now require intervention. Objective. The objective of this study was to analyze in a descriptive way the structure of the tree tomato agro-food network. Materials and methods. This study was carried out in the provinces of Cotopaxi, Tungurahua, and Chimborazo, Ecuador, during the period between the second quarter of 2016 and the end of 2017. The study applied a systemic methodology aimed at the identification and characterization of stages, agents and activities (primary and support), and the analysis of network governance mechanisms. Results. The present study showed the main social and productive characteristics, horizontal and vertical sizing; and the proposal of strategies focused on improving their productive performance. Conclusions. The inclusion of women, the sense of associativity of processors and distributors, and the training of producers in topics related to post-harvest, and good agricultural practices, would significantly improve the economic performance of the network, and also encourage greater participation of the agents involved. The network requires increasing the area allocated to tree tomato cultivation, and the application of greenhouse production systems that increase yields.